KUALITAS PELAYANAN PUBLIK DALAM PEMBUATAN IZIN TRAYEK OLEH DLLAJ KABUPATEN BOGOR - Helmi, Tedi; Munjin, R. Akhmad; Purnamasari, Irma (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2016)
The purpose of this study is: To determine the quality of service route permits by DLLAJ Bogor. The method used in this study is a survey method, whereas other types of research using descriptive method of research was conducted to determine the value of an independent variable, either one or more variables (independent) without making comparisons, or connect with other variables. The population in this study is the number of recipients of route permits issued by DLLAJ Bogor district of 72 tracks with as many as 6699 route. The sampling technique that uses Simple Random Sampling method. Analysis of the data in this study is a quantitative analysis using Likert Scale and Weight Means Score analysis formula. The results showed that the public perception of the effectiveness of service of route permits by DLLAJ Bogor Regency has been performing well, with a total score of 3.45. This means that the service delivery route permits by DLLAJ Bogor Regency indicates that the level of service has been good, but still needs to be improved in terms of both efficiency and its participatoryÂ Keyword: Quality, Service Delivery, Performance, Route Permit,